Type D personality and fear of progression among patients with first-ever stroke: the serial mediation role of perceived social support and intolerance of uncertainty - Xiaoping Yang; Lijun Wang; Xiaohui Liu; Miaomiao Chen; Yingjie Zheng; Shailing Ma; Jialin Yuan; Huijuan Wang (Frontiers in Psychology)
ObjectiveFear of progression (FoP) significantly impacts multidimensional health outcomes in stroke patients. Although Type D personality predicts FoP, mechanisms underlying the association between Type D personality and FoP remain poorly understood. This study aimed to investigate the impact of Type D personality on FoP in first-ever stroke patients and the serial mediation role of perceived social support (PSS) and intolerance of uncertainty (IU).MethodsThis cross-sectional study employed convenience sampling to recruit 300 patients with first-ever stroke (228 males and 72 females; mean age 59.52 ± 12.72 years) from two tertiary hospitals in Yinchuan, China. Participants completed the following scales: the General Information Questionnaire, the 14-item Type D scale, the Multidimensional Scale of Perceived Social Support, the Intolerance of Uncertainty Scale-12, and the Fear of Progression Questionnaire-Short Form. SPSS 24.0 was used for Harman’s single-factor test, descriptive statistics, Pearson correlation analysis, and regression analysis, with serial mediation role examined using the PROCESS macro v3.5.ResultsOur results showed that: (1) the direct effect of Type D personality on FoP was significant. (2) PSS did not independently mediate the Type D personality-FoP relationship. (3) IU significantly mediated the Type D personality-FoP relationship. (4) PSS and IU demonstrated the significant serial mediation role between Type D personality and FoP.ConclusionType D personality exerted a direct effect on FoP among first-ever stroke patients. The serial mediation model demonstrated that enhancing PSS could reduce IU, thereby alleviating FoP. Interventions targeting PSS enhancement and IU reduction constitute a promising approach to mitigate FoP in these patients, despite Type D traits’ inherent stability.